Simulation and gaming for mathematical education epistemology and teaching strategies - Piu, Angela 1971-; Fregola, Cesare; Gale Group (Hershey, Pa. Information Science Reference, 2011)
This book proposes simulation games supported by the most recent discoveries and advances in theories of learning research, and gears operational decisions toward the development of an integrated system for the teaching of mathematics in primary schools.
section 1. The teaching and learning of mathematics and the ontology of simulation games. ch 1. Epistemological framework and mathematical learning ; ch 2. Towards the construction of a system of maths teaching ; ch 3. Simulation games : onthology--Section 2. Theoretical and methodological aspects of simulation games for learning math. ch 4. Simulation games for the learning and teaching of mathematics ; ch 5. Simulation games and emotive, affective and social issues ; ch 6. Theoretical reflections on the construction of simulation games ; ch 7. Methodological proposals for simulation games : the transcoding pattern--Section 3. Design and conduct of the games. ch 8. Design of a simulation game for the learning of mathematics ; ch 9. Description of games ; ch 10. The conduct of a simulation game -- section 4. Experimental research project. ch 11. A review of previous studies ; ch 12. Research outline ; ch 13. Research results.
Electronic reproduction.
Keywords: Mathematics -- Study and teaching (Primary) -- Simulation games; Simulation games in education